Malaria-patient profile and complications at Helen Joseph hospital - Reddy, Marilyn (My University, 2016)
Background Malaria, an important parasitic disease, carries a huge burden locally and globally specifically imported malaria in non endemic industrialized regions like Gauteng. We evaluated the profile of patients treated for P. falciparum malaria at the Helen Joseph Hospital (HJH). Methods A retrospective review of 171 patient’s files was undertaken at HJH between January 2009 and December 2010. Results Imported malaria contributed to an over-whelming 96% of the population, with males accounting for 85%. Pyrexia and thrombocytopenia were the most common features. Quinine and doxycycline combination was most frequent used treatment. The number of patients with complicated and uncomplicated malaria was almost equal. Mortality rate was 5.8% (10/171). Mortality in the HIV positive and negative groups was not found to be different. Females had a higher risk of severe malaria and its complications (p < 0.005). Admission to ICU predicted an even higher mortality rate. There were four predictors of mortality in ICU patients; severe hypotension, respiratory distress and/or ARDS and lastly the need for mechanical ventilation. Conclusion Considerable progress has been made in malaria prevention and management however there are still significant prevention gaps that exist. The immense burden of imported malaria and male patient predominance was illustrated in this study. The demand for employment may have been the driving force here. The mortality rate was above national target of 0.5%. This places undue stress on the health system despite malaria being a preventable disease.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine Johannesburg, 2016